The effect of activated carbon granules and KOH solution on welding particulates and gases in air filtration - Hardita, Dwi; Wirawan, Wirawan (Jurnal Polimesin, 2023)
Hazard Identification Risk Assessment Risk Control (HIRARC) is the process of identifying hazards that can occur in routine or non-routine activities in a company or workplace, then carrying out a risk assessment of these hazards.And from the risk assessment, the hazards in the welding workshop that have a moderate risk and are interesting for researchers to innovate are from sources of danger caused by smoke resulting from welding activities, causing workers to experience respiratory problems and eye irritation. Researchers created a smoke filtration device generated from welding with a system where the welding smoke is channeled into the KOH solution to reduce the number of air particles and reduce the levels of toxic substances in the welding smoke, then to keep the KOH solution always clean, a circulation system was created through the carbon to removes dirt and keeps the solution water from being dirty and colorless.Once all the tools are ready, measurements can be made to measure several chemical elements in the welding smoke from the point before it enters the filter and after going through the filtration process. Among the elements measured are Carbon Dioxide (CO 2), Carbon Monoxide (CO), Particulate PM 2.5 (2.5 Microns), and Particulate PM 10 (10 Microns). Based on research and data testing carried out using the Anova Test and Fisher Pairwise Comparisons, it can be concluded that to produce the best and cleanest air results, the composition is K4 C1 or KOH 10% with Cabon Active 2-3 Mesh. Because if activated carbon with a mesh size larger than 2-3 mesh will affect the quality of the KOH solution because the granules are too small and contaminate the KOH solution. And the higher the KOH solution level, the more effective it is at reducing the dangerous elements in welding fumes.